Synthesis, Physical and Rheological Properties of Troger Base Polymer - Sadiq A. Karim (Journal of Global Pharma Technology, 2018)
Tröger base polymer (DM-TB) was synthesised based 4,4`-diamino-3,3`-dimethylphenylmethane (DM) via condensation polymerization for diamine monomer with dimethoxymethane in trifluoroacetic acid at room temperature. The polymerization afforded a high ratio product and white polymer with a good thermal stability.Keywords: Tröger Base Polymer; Physical and Rheological Properties.